Comparing Alternative Conceptualizations of Functional Diversity in Management Teams: Process and Performance Effects - Bunderson, J. Stuart; Sutcliffe, Kathleen M. (Academy of Management Journal, 2002)
Functional diversity in teams has been conceptualized in a variety of ways without careful attention to how different conceptualizations might lead to different results. We examined the process and performance effects of dominant function diversity (the diversity of functional experts on a team) and intrapersanal functional diversity (the aggregate functional breadth of team members). In a sample of business unit management teams, dominant function diversity had a negative, and intrapersonal functional diversity, a positive effect on information sharing and unit performance. These findings suggest that different forms of functional diversity can have very different implications for team process and performance and that intrapersonal functional diversity matters for team effectiveness.